Respective Contributions of Instrumented 3D Gait Analysis Data and Tibial Motor Nerve Block on Presurgical Spastic Equinus Foot Assessment: A Retrospective Study of 40 Adults - Cormier, Camille; Sourisseau, Clément; Montane, Emmeline; Scandella, Marino; Castel-Lacanal, Evelyne; Boissezon, Xavier De; Marque, Philippe; Gasq, David (Frontiers in Neurology, 2022)
Spastic equinus foot is a common deformity in neurologic patients that compromises walking ability. It is related to the imbalance between weak dorsiflexor and overactive plantar flexor muscles. To achieve the best functional results after surgical management, the challenge is to identify the relevant components involved in the deformity using several methods: examination in supine position, motor nerve blocks allowing a transient anesthesia of suspected overactive muscles, and kinematic and electromyographic data collected during an instrumented 3D gait analysis. The procedure is not standardized, its use varying from one team to another. Access to gait analysis laboratories is limited, and some teams do not perform motor nerve blocks. When both examinations are available, instrumental data from the instrumented 3D gait analysis can be used to specify muscle targets for motor blocks, but data collected from both examinations are sometimes considered redundant. This retrospective cohort analysis compared examination in supine position, temporary motor nerve blocks and instrumented 3D gait analysis data in 40 adults after brain or spinal cord injuries. Clinical data collected before motor nerve block was not associated with instrumental data to assess calf muscles overactivity and tibialis anterior function. Improvement of ankle dorsiflexion in the swing phase after tibial motor nerve block was associated with soleus spastic co-contraction during this phase corroborating its involvement on ankle dorsiflexion defect. This study showed the relevance of tibial motor nerve block to remove spastic calf dystonia and facilitate the assessment of calf contracture. It also underlined the need for complementary and specific analyses of the tibialis anterior abnormal activation pattern after motor nerve block to confirm or deny their pathological nature.